POLISEMI PADA WACANA HUMOR INDONESIA LAWAK KLUB - Zulfatun Anisah (Al Hikmah: Jurnal Studi Keislaman, 2016)
This study focused on (1) the form of polysemy in the discourse of ILK humor (2) the relation of meaning in ILK humor discourse, and (3) the cause of meaning multiplicity in ILK humor discourse. Based on the previous focus, the purposes of this study were (1) to find the polysemy forms in the discourse of ILK humor, (2) to find a relation of meaning in ILK humor discourse, and (3) to find a multiplicity of meaning in ILK humor discourse. The data in this study were gathered through the stages of video downloads, transcription of data, the selection of data, and sorting of data. The instruments of this study were divided into two; they were data collection and data analysis. In the data collection, the instrument used in this study was a non-test instrument, called documentation. The documentation here was in the form of speeches in the ILK video which were transcribed. The Instruments of analyzing the data in this study consisted of researchers, data cards, and notebook research. The researcher was as a major instrument in analyzing the data. The researcher acted as an analyzer of data findings. The data collection technique used in this research were documentary and observation. In analyzing the data, the used techniques were agih and frontier methods along with their techniques. The results of this study were 37 forms of speech which had a new meaning, included words and combinations of words.